Indonesian Language Learning in Elementary Schools Through Life Skills Education Model - Egah Linggasari; Endi Rochaendi (LITERASI (Jurnal Ilmu Pendidikan), 2022)
This research is a needs analysis research which will be used as the basis for personality factors in learning Indonesian. The purpose of this research is to describe Indonesian language learning in elementary schools through a life skills education model. The research method used is library research, whose data sources come from relevant previous research data in the form of textbooks, books, journal articles and other published manuscripts. The results of the study show that learning Indonesian in elementary schools through life skills education is more empowered in developing the communication potential of Indonesian both oral and written and can develop language skills (listening skills, reading skills, speaking skills and writing skills) which are very useful in perform communication interactions. In communicating activities, language skills are not carried out singly, but are used together to achieve communication goals. Another finding is that the learning process activities are used for the purpose of training students to use Indonesian more for communication purposes, and not being required to master more knowledge of Indonesian. As an effort to optimize learning Indonesian, it is necessary to create conditions for self-directed learning for students.Keywords: Learning, Indonesian Language, Life Skills Education.